2019
DOI: 10.1111/bph.14589
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological impact of antiretroviral therapy on platelet function to investigate human immunodeficiency virus‐associated cardiovascular risk

Abstract: Background and purpose: Some clinical studies have reported increased myocardial infarction in people living with human immunodeficiency virus (HIV) taking the antiretroviral abacavir sulphate (ABC). Given that clinical studies contain confounding variables (e.g., HIV-associated factors), we investigated the pharmacological effects of antiretrovirals on platelet function in HIV-negative volunteers in order to identify mechanisms of increased cardiovascular risk.Experimental approach: Platelets were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…Even though these NRTIs are known to have lower mitochondrial toxicity 1 , it is unclear whether long-term treatment does not exert any cumulative reduction in mtDNA pl too. While ABC-use has been linked to platelet perturbations in multiple studies [43][44][45] , others could not confirm ABC associated platelet dysfunction 35,46 . In our study, neither mtDNA pl content nor platelet function were associated with current or prior ABC-use.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these NRTIs are known to have lower mitochondrial toxicity 1 , it is unclear whether long-term treatment does not exert any cumulative reduction in mtDNA pl too. While ABC-use has been linked to platelet perturbations in multiple studies [43][44][45] , others could not confirm ABC associated platelet dysfunction 35,46 . In our study, neither mtDNA pl content nor platelet function were associated with current or prior ABC-use.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments, stimulation with abacavir or its metabolite carbovir-triphosphate has been shown to potentiate platelet degranulation and aggregation in response to prothrombotic agonists 89,90 . Mechanistically, stimulation with abacavir or carbovir-triphosphate has been shown to competitively inhibit the activity of guanylyl cyclase when compared to non-guanosine nucleotide analogues, preventing the inhibitory effect of NO, a major negative-regulator of platelet activation 89,90 . Interestingly, we observed increased NO synthesis in platelets from HIV + dengue coinfected patients when compared to patients infected with DENV only.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, following oral administration of abacavir, the nitric oxide (NO)-induced increase of platelet cGMP was blunted, potentially explaining the dose-dependent enhancement in platelet aggregation (143,145). While some reports failed to detect stimulatory effects of abacavir on platelets (146,147), most of the aforementioned studies, including those that found that abacavir caused platelet granule release in vitro (148), appear to support the involvement of abacavir in the augmentation of platelet function, both in vitro and in vivo, whereas tenofovir-based therapies had no effect (148). In this context, Taylor et al conclude that "these observations could explain epidemiological and clinical observations linking abacavir with increased incidence of platelet-driven cardiovascular events such as myocardial infarction" (148).…”
Section: Nucleos(t)ide and Non-nucleoside Reverse Transcriptase Inhibmentioning
confidence: 99%